How might people near national roads be affected by traffic noise as electric vehicles increase in number? A laboratory study of subjective evaluations of environmental noise - Walker I.; Kennedy J.; Martin S.; Rice H. (My University, 2016)
We face a likely shift to electric vehicles (EVs) but the environmental and human consequences of this are not yet well understood. Simulated auditory traffic scenes were synthesized from recordings of real conventional and EVs. These sounded similar to what might be heard by a person near a major national road. Versions of the simulation had 0%, 20%, 40%, 60%, 80% and 100% EVs. Participants heard the auditory scenes in random order, rating each on five perceptual dimensions such as pleasant-unpleasant and relaxing stressful. Ratings of traffic noise were, overall, towards the negative end of these scales, but improved significantly when there were high proportions of EVs in the traffic mix, particularly when there were 80% or 100% EVs. This suggests a shift towards a high proportion of EVs is likely to improve the subjective experiences of people exposed to traffic noise from major roads. The effects were not a simple result of EVs being quieter: ratings of bandpassfiltered versions of the recordings suggested that people's perceptions of traffic noise were specifically influenced by energy in the 500-2000 Hz band. Engineering countermeasures to reduce noise in this band might be effective for improving the subjective experience of people living or working near major roads, even for conventional vehicles; energy in the 0-100 Hz band was particularly associated with people identifying sound as quiet and, again, this might feed into engineering to reduce the impact of traffic noise on people.
Keywords: Traffic Noise